An assessment of the technology innovation initiatives in the Indian small-scale manufacturing industry. (20th May 2009) - Nanda, Tarun; Singh, T.P.
The fierce competition arising out of globalisation and liberalisation is forcing organisations across the world to realise that their survival is not feasible in the absence of Research and Development (R&D) and innovation practices. It is high time that manufacturing organisations wake up and gear up for R&D initiatives to develop cutting-edge technologies for sustained competitive advantage. Technology Development (TD) initiatives have become mandatory for the industrial growth, strategic self-reliance and sustained competitiveness of an enterprise and must be placed within the context of market opportunities, customer needs and strategic direction, thereby leading to improving the product and technology portfolio. The literature highlights that there are five key components to appraise the technology innovation initiatives in the manufacturing sector. The present research is aimed at developing an insight into the prevalent TD practices adopted in the contemporary Indian manufacturing industry for realising the sustainable growth and development of the industrial sector. The study highlights the performance of Indian manufacturing organisations in different components of Technology Development Implementation Programmes (TD Programmes) to make a significant organisational transformation from a technology-dependent regime to the proactive adaptation of technology innovation initiatives for affecting organisational performance improvements.